And now for something completely different: looking ahead to new encryption and secrecy protocols - Ashman, Helen; Gilbert, Martyn (2001)
Transmitting sensitive data over non-secret channels has always required encryption technologies to ensure that the data arrives without exposure to eavesdroppers. The Internet has made it possible to transmit vast volumes of data more rapidly and cheaply and to a wider audience than ever before. At the same time, strong encryption makes it possible to send data securely, to digitally sign it, to prove it was sent or received, and to guarantee its integrity.